The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1021/jm00035a008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure-Activity Relationships, and Pharmacological Evaluation of a Series of Fluorinated 3-Benzyl-5-Indolecarboxamides: Identification of 4-[[5-[((2R)-2-Methyl-4,4,4-trifluorobutyl)carbamoyl]-1-methylindol-3-yl]methyl]-3methoxy-N-[(2-methylphenyl)sulfonyl]benzamide, a Potent, Orally Active Antagonist of Leukotrienes D4 and E4

Abstract: The continued exploration of a series of 3-(arylmethyl)-1H-indole-5-carboxamides by the introduction of fluorinated amide substituents has resulted in the discovery of 4-[[5-[((2R)-2-methyl-4,4,4-trifluorobutyl)carbamoyl]-1-methyli ndol- 3-yl]methyl]-3-methoxy-N-[(2-methyl-phenyl)sulfonyl]benzamide (38p, ZENECA ZD3523), which has been chosen for clinical evaluation. This compound exhibited a Ki of 0.42 nM for displacement of [3H]LTD4 on guinea pig lung membranes, a pKB of 10.13 +/- 0.14 versus LTE4 on guinea p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In this context, γ-trifluoromethylated amines are a unique class of compounds of important biological activities. For example, γ-CF 3 -substituted amine Zeneca ZD 3523 ( 1 ) is a potent, orally active antagonist of leukotrienes D 4 and E 4 discovered by the Zeneca Pharmaceutical Co . Another example is that 3-(trifluoromethyl)-3-arylpropylamine 2 has been identified as a powerful inhibitor of retinol dehydrogenases for treating ophthalmic diseases and disorders .…”
mentioning
confidence: 99%
“…In this context, γ-trifluoromethylated amines are a unique class of compounds of important biological activities. For example, γ-CF 3 -substituted amine Zeneca ZD 3523 ( 1 ) is a potent, orally active antagonist of leukotrienes D 4 and E 4 discovered by the Zeneca Pharmaceutical Co . Another example is that 3-(trifluoromethyl)-3-arylpropylamine 2 has been identified as a powerful inhibitor of retinol dehydrogenases for treating ophthalmic diseases and disorders .…”
mentioning
confidence: 99%
“… 17 Similarly, β-alkyl-substituted chiral amines, and in particular trifluoromethylated ones, are known precursors in the synthesis of leukotriene receptor antagonists used, for instance, to treat asthma. 18 To showcase the utility of our catalytic protocol, we demonstrated that chiral β-substituted amide 2e can easily be transformed into a number of corresponding valuable molecules ( Figure 1 c). Deprotection 19 of 2e afforded chiral β-ethyl amide 4 , which in turn can be used for the synthesis of the chiral γ-ethyl chiral amine 5 via reduction of the carbonyl moiety or to β-ethyl chiral amine 6 through Hoffman rearrangement.…”
Section: Resultsmentioning
confidence: 97%
“…When subjected to deprotection and Hoffman rearrangement, this product could lead to a direct precursor of the drug candidate ZENECA ZD 3523. 18 Another synthetically important transformation in which this catalytic system can be engaged is the trapping of the product enolate ( Figure 1 e). To demonstrate this, we performed the CA reaction to Br-substituted enamide 1w .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent hydrolysis of 3a delivered β-CF 3 -amine 4a in 73% yield (eq ). The two-step method provides a convenient and efficient entry to 4a , a key structural motif to increase leukotriene antagonist activity, whose synthesis required six steps starting from diethyl malonate according to the literature . Similarly, the aminotrifluoromethylation of methyl but-3-enoate followed by acid hydrolysis led to the efficient and rapid synthesis of β-trifluoromethylated GABA ( 4b ), a potential drug candidate (eq 2 ).…”
mentioning
confidence: 99%